2015
DOI: 10.1186/s12913-015-0701-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of the intrauterine device among family planning providers in Nepal: a cross-sectional analysis by cadre and sector

Abstract: BackgroundNepal has high unmet need for family planning and low use of intrauterine devices (IUDs). While clients’ attitudes toward the IUD are known in a variety of contexts, little is known about providers’ knowledge and perceptions of the IUD in developing countries. Nepal’s liberal IUD service provision policies allow the opportunity to explore provider knowledge and perceptions across cadres and sectors. This research contributes to an understanding of providers’ IUD perceptions in low-resource environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 25 publications
4
24
2
2
Order By: Relevance
“…This finding was similar to the study outcome in Nepal 8. The providers’ knowledge also correlates to the workload of the facility, which is translated into the number of patients seen per week.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding was similar to the study outcome in Nepal 8. The providers’ knowledge also correlates to the workload of the facility, which is translated into the number of patients seen per week.…”
Section: Discussionsupporting
confidence: 84%
“…Objectively, our study was an adaptation from a survey among nurses as contraception providers in Nepal 8. Surprisingly, our results showed a lower percentage of all correct answers, suggesting a serious knowledge gap among our doctors.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…7 A study conducted by Keerti et al 8 regarding knowledge on emergency contraception among nursing students it was found that 55.71% students gave the correct response to ideal clients for emergency contraception. A study by Chakraborty et al 9 found that between 20% and 35% of providers consider the common side effects of painful menstruation, cramping, and excessive bleeding unacceptable while in this study bleeding and infection are the most common side effects associated with IUD. In a study by Eve Espel et al, overall 69-78% of providers had good factual knowledge about the IUD and felt adequately prepared to insert a device or counsel women about it whereas in this study 92% were aware about side effects and when to insert an IUD.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the following covariates because previous surveys of U.S. physicians and nurse practitioners have indicated that they may be associated with perceptions of IUD safety for women with HIV: primary clinical focus of public‐sector providers and specialty of office‐based physicians, clinical setting, years out of training and training in IUD insertion . Other covariates included were occupation (physician, registered nurse or midlevel practitioner, the last category comprising physician assistants, certified nurse‐midwives and nurse practitioners); working at a Title X–funded clinic (for public‐sector providers); use of U.S. MEC in clinical practice (based on use of related materials, such as tools or documents); region of practice (based on U.S. Census Bureau definitions); gender; and the proportions of female patients of reproductive age who receive family planning services, receive Medicaid or other public assistance to cover medical services, belong to racial or ethnic minority groups, are not English‐speaking, and are 19 or younger.…”
Section: Methodsmentioning
confidence: 99%